Ответ:
-5
Пошаговое объяснение:
(1/(x-y))((x+(-))/(-))+2/(+)=(1/(x-y))(x(+)-y(+))/(-)+2/(+)=(1/(x-y))(x-y)(+)/(-)+2/(+)=(+)²/(x-y)+2/(+)=(x+2x+y)/(x-y)
Делим числитель и знаменатель на х получается -5
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
-5
Пошаговое объяснение:
(1/(x-y))((x
+
(
-
))/(
-
))+2
/(
+
)=(1/(x-y))(x(
+
)-y(
+
))/(
-
)+2
/(
+
)=(1/(x-y))(x-y)(
+
)/(
-
)+2
/(
+
)=(
+
)²/(x-y)+2
/(
+
)=(x+2x+y)/(x-y)
Делим числитель и знаменатель на х получается -5